THE HEAD OF JANUS: HERMENEUTICS AND DECONSTRUCTION IN GADAMER AND DERRIDA BETWEEN AGREEMENT AND DISAGREEMENT - Simona VENEZIA (Studia Universitatis Babeș-Bolyai. Philosophia, 2019)
The Head of Janus: Hermeneutics and Deconstruction in Gadamer and Derrida between Agreement and Disagreement. The paper aims to discuss the complexity of the relationship between Gadamer’s Hermeneutics and Derrida’s Deconstruction in order to remove the usual opposition between these two thinkers and their philosophical perspectives. It is possible to build a collaboration against every idealistic and subjectivist foundation moving from the hermeneutic-deconstructive interaction between the concepts of identity and difference, understanding and sense, writing and reading etc. Only in this way can the so-called improbable debate become an un-interrupted dialogue: the distance ceases to be an insuperable obstacle and becomes an openness of sense.